Light and electron microscopic observations on the organization of skin and associated glands of two caecilian amphibians from Western Ghats of India. (March 2018) - Damodaran, Arun; Reston Saroja, Beyo; Kotharambath, Ramachandran; Mohammad Abdulkader, Akbarsha; Oommen, Oommen V.; Lekha, Divya
Highlights: Light and electron microscopic study of skin of Ichthyophis tricolor and Uraeotyphlus cf. oxyurus . Mucous and granular glands are reported. First report on caecilians from Western Ghats, India. Abstract: We adopted light and electron microscopy to understand the structure of the skin of two species of caecilians, Ichthyophis tricolor and Uraeotyphlus cf. oxyurus, from Western Ghats of Kerala, India. The surface of the skin of these caecilians contains an irregular pattern of microridges. Oval, round and polymorphic glandular openings are randomly distributed all over the skin surface. Most of the openings are funnel shaped. The epithelial cells along the rim of the opening descend into the tunnel of the duct. A few glandular openings protrude slightly above the epithelium of the duct. The skin is formed of epidermis and dermis. Small flat disk-like dermal scales, composed of a basal plate of several layers of unmineralized collagen fibers topped with a discontinuous layer of mineralized globular squamulae, are lodged in pouches in the transverse ridges of the skin. Each pouch contains 1–4 scales, which might differ in size. The scales are almost similar between species, yet the difference can be useful in distinguishing between the two species. Flask cells and Merkel cells are present in the epidermis. Two types of glands, mucous and granular, are present in the dermis. The mucous glands are densely packed with mucous vesicles. Darkly stained mucous producing cells are located around the periphery of the gland. Secretory mucous vesicles differ in their organization and distribution. The granular glands are located perpendicular to the skin surface. The granule producing cells of the gland are located near the periphery. There are differently stained spherical secretory granules of various sizes in the cytoplasm. Thus, the use of different microscopic techniques contributed fascinatingly to the first ever understanding of organization of the skin of two selected caecilian species from Western Ghats, revealing certain features to differ between them.